The Association of Lipoprotein(a) and Circulating Monocyte Subsets with Severe Coronary Atherosclerosis - Afanasieva, Olga I. (J Cardiovasc Dev Dis, 2021)
Background and aims: Chronic inflammation associated with the uncontrolled activation of innate and acquired immunity plays a fundamental role in all stages of atherogenesis. Monocytes are a heterogeneous population and each subset contributes differently to the inflammatory process. A high level of lipoprotein(a) (Lp(a)) is a proven cardiovascular risk factor. The aim of the study was to investigate the association between the increased concentration of Lp(a) and monocyte subpopulations in patients with a different severity of coronary atherosclerosis. Methods: 150 patients (124 males) with a median age of 60 years undergoing a coronary angiography were enrolled. Lipids, Lp(a), autoantibodies, blood cell counts and monocyte subpopulations (classical, intermediate, non-classical) were analyzed. Results: The patients were divided into two groups depending on the Lp(a) concentration: normal Lp(a) < 30 mg/dL (n = 82) and hyperLp(a) ≥ 30 mg/dL (n = 68). Patients of both groups were comparable by risk factors, autoantibody levels and blood cell counts. In patients with hyperlipoproteinemia(a) the content (absolute and relative) of non-classical monocytes was higher (71.0 (56.6; 105.7) vs. 62.2 (45.7; 82.4) 10(3)/mL and 17.7 (13.0; 23.3) vs. 15.1 (11.4; 19.4) %, respectively, p < 0.05). The association of the relative content of non-classical monocytes with the Lp(a) concentration retained a statistical significance when adjusted for gender and age (r = 0.18, p = 0.03). The severity of coronary atherosclerosis was associated with the Lp(a) concentration as well as the relative and absolute (p < 0.05) content of classical monocytes. The high content of non-classical monocytes (OR = 3.5, 95% CI 1.2–10.8) as well as intermediate monocytes (OR = 8.7, 2.5–30.6) in patients with hyperlipoproteinemia(a) were associated with triple-vessel coronary disease compared with patients with a normal Lp(a) level and a low content of monocytes. Conclusion: Hyperlipoproteinemia(a) and a decreased quantity of classical monocytes were associated with the severity of coronary atherosclerosis. The expansion of CD16+ monocytes (intermediate and non-classical) in the presence of hyperlipoproteinemia(a) significantly increased the risk of triple-vessel coronary disease.